Development Strategy Of Omah Kopi Banyuwangi Luwak Coffee Business - Setyawan, Bagus; Utami, Arfiati Ulfa; Ulfa, Rosiana; Arista, Yuvita Lira (Syarif Hidayatullah State Islamic University Jakarta, 2024)
Luwak coffee is one type of coffee that is currently one of the most popular variants for coffee-loving consumers. The existence of civet coffee-based businesses is also increasing, including the Kopi Luwak business Omah Kopi in Banyuwangi. The number of civet coffee processing agro-industries that have sprung up, technological developments and people's lifestyles make the Luwak Coffee Agroindustry